Effect of Melatonin Implants during the Non-Breeding Season on the Onset of Ovarian Activity and the Plasma Prolactin in Dromedary Camel - El Allali, Khalid; Sghiri, Abdelmalek; Bouâouda, Hanan; Achaâban, Mohamed Rachid; Ouzir, Mounir; Bothorel, Béatrice; El Mzibri, Mohammed; El Abbadi, Najia; Moutaouakkil, Adnane; Tibary, Ahmed; Pévet, Paul (Frontiers in Veterinary Science, 2018)
To examine a possible control of reproductive seasonality by melatonin, continual-release subcutaneous melatonin implants were inserted 4.5 months before the natural breeding season (October-April) into female camels (Melatonin-treated group). The animals were exposed to an artificial long photoperiod (16L:8D) for 41 days prior to implant placement to facilitate receptivity to the short-day signal that is expected with melatonin implants. The treated and control groups (untreated females) were maintained separately under outdoor natural conditions. Ovarian follicular development was monitored in both groups by transrectal ultrasonography and by plasma estradiol-17β concentrations performed weekly for 8 weeks and then on week 14 following implant insertion. Plasma prolactin concentrations were determined at 45 and 15 days before and 0, 14, 28, 56 and 98 days after implant insertion. Plasma melatonin concentration was determined to validate response to the artificial long photoperiod and to verify the pattern of release from the implants. Results showed that the artificial long photoperiod induced a melatonin secretion peak of significantly (P<0.05) shorter duration (about 2.5 hours). Melatonin release from the implants resulted in higher circulating plasma melatonin levels during day-time and night-time which persisted for more than 12 weeks following implants insertion. Treatment with melatonin implants advanced the onset of follicular growth activity by 3.5 months compared to untreated animals. Plasma estradiol 17ß increased gradually from the 2nd week after the beginning of treatment to reach significantly (P<0.01) higher concentrations (39.2±6.2 to 46.4±4.5 pg/ml) between the 3rd and the 5th week post insertion of melatonin implants. Treatment with melatonin implants also induced a moderate but significant (P<0.05) suppressive effect on plasma prolactin concentration on the 28th day. These results demonstrate that photoperiod appears to be involved in dromedary reproductive seasonality. Melatonin implants may be a useful tool to manipulate seasonality and to improve reproductive performance in this species. Administration of subcutaneous melatonin implants during the transition period to the breeding season following an artificial signal of long photoperiod have the potential to advance the breeding season in camels by about 2.5 months.